Hyperheuristic based migrating birds optimization algorithm for a fairness oriented shift scheduling problem - ALP, GÖZDE; ALKAYA, ALİ FUAT (My University, 2021)
The purpose of this paper is twofold. First, it introduces a new hybrid computational intelligence algorithm to the optimization community. This novel hybrid algorithm has hyperheuristic (HH) neighborhood search movements embedded into a recently introduced migrating birds optimization (MBO) algorithm. Therefore, it is called HHMBO. Second, it gives the necessary mathematical model for a shift scheduling problem of a manufacturing company defined by including the fairness perspective, which is typically ignored especially in manufacturing industry. Therefore, we call this complex optimization problem fairness oriented integrated shift scheduling problem (FOSSP). HHMBO is applied on FOSSP and is compared with the well-known simulated annealing, hyperheuristics, and classical MBO algorithms through extended computational experiments on several synthetic datasets. Experiments demonstrate that the new hybrid computational intelligence algorithm is promising especially for large sized instances of the specific problem defined here. HHMBO has a high exploration capability and is a promising technique for all optimization problems. To justify this assertion, we applied HHMBO to the well-known quadratic assignment problem (QAP) instances from the QAPLIB. HHMBO was up to 14.6% better than MBO on converging to the best known solutions for QAP benchmark instances with different densities. We believe that the novel hybrid method and the fairness oriented model presented in this study will give new insights to the decision-makers in the industry as well as to the researchers from several disciplines.
Keywords: Harita Mühendisliği-Geomatik; Mühendislik ve Teknoloji; Geotechnical Engineering; Engineering and Technology; MÜHENDİSLİK, ÇOK DİSİPLİNLİ; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); MATEMATİK, DİSİPLİNLERARASI UYGULAMALAR; Matematik; Temel Bilimler (SCI); ENGINEERING, MULTIDISCIPLINARY; ENGINEERING; Engineering, Computing & Technology (ENG); MATHEMATICS, INTERDISCIPLINARY APPLICATIONS; MATHEMATICS; Natural Sciences (SCI); Analiz; Genel Mühendislik; Cebir ve Sayı Teorisi; Hesaplamalı Matematik; Matematik (çeşitli); Mühendislik (çeşitli); Medya Teknolojisi; Genel Matematik; Fizik Bilimleri; Analysis; General Engineering; Algebra and Number Theory; Computational Mathematics; Mathematics (miscellaneous); Engineering (miscellaneous); Media Technology; General Mathematics; Physical Sciences